Effect of a 6-week wrestling and wrestling-technique based circuit exercise on plasma lipoprotein profiles and hormone levels in well-trained wrestlers - Rashidlamir, A.; Ghanbari-Niaki, A. (International Journal of Wrestling Science, 2011)
The effect of 6 weeks of wrestling and wrestling.technique based circuit exercise on the plasma lipoprotein profile and selected hormonal changes was examined in 20 well-trained senior wrestlers. Subjects were randomly divided into two groups, an experimental group participated in 6 weeks of wrestling and wrestling.technique based circuit exercise (WTBCE) and the control group that remained sedentary. Blood samples were taken 48 hours before and after the first and last session of exercise training, respectively. Growth hormone (GH), insulin-like growth factor (IGF-1), testosterone, cortisol, insulin, cholesterol, HDL, LDL, triglycerides (TG), fasting blood sugar (FBS), plasma volume (PV), body weight, body mass index (BMI), body fat, maximum power, fatigue index and VO2max were measured. In the experimental group, significant decreases were observed in fasting FBS, IGF-1, GH, insulin, cortisol, PV, body weight, BMI, and body fat. Significant increases were observed in testosterone, maximum power, fatigue index and VO2max. No significant changes in cholesterol, HDL, LDL and TG, were seen in the experimental group. However, when the data was adjusted for the mean decrease of plasma volume in the exercise group, it was shown that cholesterol and HDL decreased significantly (p<0.05). There were no significant changes observed in the control group. We concluded that the significant decreases, especially in GH and IGF-1 can affect senior wrestlers. growth during the in-season training.